Alkynylgold(I) C3‐Chiral Concave Complexes: Aggregation and Luminescence. Issue 7 (27th December 2021) - Zhang, Jing; Schaly, Astrid; Chambron, Jean‐Claude; Vincent, Bruno; Zorn, Nathalie; Leize‐Wagner, Emmanuelle; Jean, Marion; Vanthuyne, Nicolas
Abstract: Chiral gold(I) acetylide trinuclear complexes 1 –3 based on the cyclotribenzylene platform and terminal PR3 ligands (R=Ph, Et, and Cy, respectively), were characterized and their light emission studied. They exhibited long‐lived blue phosphorescence in CHCl3 and a weak fluorescence in the UV. In MeOH/CHCl3 mixtures of >1:1 volume ratio, 1 and 2 exhibited a new emission band at ca. 540 nm that developed at the expense of the UV emission. DLS studies demonstrated the presence of molecular aggregates of Ø 30–80 nm. The green emission observed in MeOH‐rich solvent mixtures was therefore induced by aggregation, and could originate from Au⋅⋅⋅Au interactions. The AIE spectrum of 3 was observed only in solutions containing 99 % of MeOH, and correlated with its solid state emission. The AIE profiles of the enantiomers of 1 differed from that of rac ‐1, suggesting that the latter is a true racemate. Abstract : Alkynylgold(I) C 3 ‐symmetric complexes bearing triphenyl (1 ) and trialkyl phosphine ligands (2 and 3 ) were synthesized and studied. In CHCl3 /MeOH mixtures 1 and 2 showed an AIE effect at 540 nm, probably originating from aurophilic interactions. 3 showed AIE only in nearly pure MeOH and in the solid state. The aggregation of optically pure 1 started at lower MeOH content than (±)‐1, indicating that the latter gave racemates rather than conglomerates.